UPAYA PENINGKATAN PELAYANAN ADMINISTRASI AKADEMIK MELALUI SISTEM KOMPUTERISASI DATA ADMINISTRASI AKADEMIK DI UNIVERSITAS NEGERI MEDAN (UNIMED) - Rahman1, Arif (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2006)
Nowadays, computer-based administration system seems to have embeded to college services. Furthermore, computerization of academic data management for various purposes has become common attention. One thing, which is important with regard to the management of academic data, is that each data typology should function as a reference. In this research, the problem formulation includes: (1) what strategy is implemented to develop a computer-based data administration system in effort to accomplish Management Information System; and (2) whether the appointed team for developing the UNIMED computer-based academic administration system has worked based upon the strategy.